Kanski's Clinical Ophthalmology: a systematic approach - Bowling, B. Brad (International edition, 2016)
Kanski's Clinical Ophthalmology: A Systematic Approach is the classic specialty text providing the perfect ophthalmology foundation for trainees through to experienced practitioners. The famous visually dynamic and succinct format enables easy comprehension and focused guidance in the diagnosis and management of ophthalmic disorders.